ANALYSIS OF CURRENT APPROACHES TO THE TREATMENT OF TYPE TWO DIABETES (Physical Culture and Sport: Scientific Perspective, 2025)
The article reviews modern approaches to the treatment of type two diabetes mellitus as one of the most relevant chronic diseases in the world and in Ukraine. Type two diabetes, which accounts for the majority of all diabetes cases, is a serious global health problem. Diabetes mellitus is an endocrine and metabolic disease that occurs as a result of the influence of endogenous and exogenous factors. Its development is associated with absolute or insufficient insulin deficiency, which leads to metabolic disorders in the body. It is emphasized that the disease covers all age groups of the population, and its spread is largely due to negative changes in lifestyle, in particular, physical inactivity, unbalanced nutrition, excess body weight, as well as the impact of chronic stress, especially in conditions of martial law. The clinical recommendations of the American Diabetes Association, the World Health Organization and national treatment standards are analyzed. The paper analyzes the key provisions of international and national clinical recommendations for the treatment of type two diabetes mellitus. It is noted that the first and mandatory stage is a change in lifestyle, which includes diet therapy, physical activity, modification of behavioral habits and the formation of self-control. The feasibility of early prescribing metformin as a first-line drug is substantiated, with subsequent individualized expansion of pharmacotherapy depending on the degree of compensation and concomitant diseases. A generalized classification of treatment methods based on the combined use of drug and non-drug strategies is presented. It is noted that a comprehensive approach contributes not only to the stabilization of glycemia, but also prevents the development of complications, improves quality of life and adherence to treatment. The importance of staged, evidence-based therapy taking into account the individual needs of the patient is emphasized, as well as the importance of multidisciplinary interaction of medical specialists to achieve sustainable glycemic control and prevention of complications.
Keywords: type two diabetes; treatment; glycemia; complications